Potential analysis of Asian toad (Duttaphrynus melanostictus) as a controller of harmful insects and their substitutions in elementary school science lessons - Muhammad Syazali; I Putu Artayasa; Mohammad Liwa Ilhamdi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The house toad (Duttaphrynus melanostictus) is a highly adaptable amphibian species, and is commonly found in urban areas. On Lombok Island, this species has the highest abundance in non-forest habitat types. In their habit, amphibians function as predators of various types of insects and various types of invertebrates. There are several research reports on prey items from Duttaphrynus melanostictus, but information regarding its role as control of harmful insects is still limited, especially on the island of Lombok. On the other hand, science learning aims to introduce the surrounding environment to students. Therefore, integrating the roles of species commonly found in these settlements is a necessity. The purpose of this study was to analyze the potential of Duttaphrynus melanostictus as a pest control insect, and its urgency in science learning, especially in elementary schools. The study was conducted using gastric surgery analysis method. The frog's stomach was taken continuously until the data was saturated, i.e. the data obtained were the same as the previous surgeries. The results showed that Duttaphrynus melanostictus preyed on 14 types of insects. There are 12 species (85.71%) of which are harmful insects. If classified, 9 species (75%) are insect pests, and 3 species (25%) are disease vectors. Information on the role of this species can be substituted for science lessons in elementary school. The appropriate topics are (1) the importance of balancing and preserving natural resources in the environment, and (2) the relationship between ecosystem components and food webs in the surrounding environment.